Au Based Ni and Co Bimetallic Core Shell Nanocatalysts for Room Temperature Selective Decomposition of Hydrous Hydrazine to Hydrogen. Issue 9 (4th March 2019) - Jain, P.; Anila, K. A.; Vinod, C. P.
Abstract: Nickel and Cobalt bimetallic catalysts with Au as core metal has been synthesized and demonstrated for hydrazine decomposition reaction for producing hydrogen. Gold‐cobalt and gold nickel bimetallic system belonging to the class of strained structures with high lattice mismatch of approximately 14% are demonstrated for synergistic effects atypical of monometallic counterparts for the selective decomposition of hydrous hydrazine to H2 with N2 as the other product at room temperature. Abstract : Decomposition of hydrous hydrazine is reported on Co and Ni bimetallic nanoparticles modified with Au in a core‐shell geometry. The results demonstrate that 100% selectivity for H2 can be tuned by forming Au@Co bimetallic architecture whereas Ni can be made room temperature active for hydrazine decomposition in Au@Ni geometry. The catalysts were also found to be recyclable without loss in activity.